2021
DOI: 10.14814/phy2.15062
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation‐induced left ventricular fibrosis is partially mediated by tumor necrosis factor‐α

Abstract: Objective To determine the mechanisms of inflammation‐induced left ventricular (LV) remodeling and effects of blocking circulating tumor necrosis factor alpha (TNF‐α) in a model of systemic inflammation. Methods Seventy Sprague‐Dawley rats were divided into three groups: the control group, the collagen‐induced arthritis (CIA) group, and the anti‐TNF‐α group. Inflammation was induced in the CIA and anti‐TNF‐α groups. Following the onset of arthritis, the anti‐TNF‐α group received the TNF‐α inhibitor, etanercept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 54 publications
2
8
0
Order By: Relevance
“…Microvascular inflammation resulting from increased expression of cell adhesion molecules, including VCAM1, promotes leukocyte transmigration [29,30] and enhances ROS production, which are characteristic of an oxidative stress environment [31][32][33]. Supporting this, we previously showed that collagen inoculation increased CD68 expression in LV tissues, showing infiltration of leukocytes [26]. In the present study, PTX3 and iNOS expression was increased in CIA rats, further indicating leukocyte infiltration in the heart tissues and hence local inflammation.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Microvascular inflammation resulting from increased expression of cell adhesion molecules, including VCAM1, promotes leukocyte transmigration [29,30] and enhances ROS production, which are characteristic of an oxidative stress environment [31][32][33]. Supporting this, we previously showed that collagen inoculation increased CD68 expression in LV tissues, showing infiltration of leukocytes [26]. In the present study, PTX3 and iNOS expression was increased in CIA rats, further indicating leukocyte infiltration in the heart tissues and hence local inflammation.…”
Section: Discussionsupporting
confidence: 82%
“…Circulating CRP concentrations were lower in the CIA + anti-TNF-α group compared to the CIA group (p = 0.05). LV diastolic function was significantly impaired in the CIA and CIA + anti-TNF-α groups (Table 1), as previously reported [24,26]. Briefly, lateral wall e′, e′/a′ and E/e′ were significantly impaired in both groups of rats inoculated with collagen compared to the control group (Table 1).…”
Section: Body Mass Blood Pressure Markers Of Inflammation and Diastol...supporting
confidence: 84%
See 2 more Smart Citations
“…5 Adverse extracellular matrix remodeling 16 and hypophosphorylation of the giant spring protein, titin, 17 contribute to passive myocardial stiffness, which affects the ability of the heart to relax during diastole. We have previously shown that rats with CIA have increased profibrotic gene expression LV fibrosis 18 and disrupted expression of genes that regulate titin phosphorylation, 19 showing that systemic inflammation disrupts the passive processes of diastolic function. However, it is not known whether the active process of diastole is affected by the systemic inflammation in rats with CIA.…”
Section: Introductionmentioning
confidence: 99%